2005
DOI: 10.1002/ijc.21035
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of S100A2 protein as a prognostic marker for patients with stage I non small cell lung cancer

Abstract: S100A2, a calcium‐binding protein, recently became of major interest because of its differential expression during transformation and metastasis in various tumors. The purpose of this study was to investigate the prognostic significance of S100A2 expression in the early‐stage non small lung cancer (NSCLC). Immunohistochemical analysis to determine the percentage of cells staining positive for S100A2 was performed on 11 NSCLC tissue microarray slides containing samples from 113 patients with pathologic stage I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 42 publications
3
50
1
Order By: Relevance
“…Positive Ki-67 expression was found to correlate with positive expression of both KCIP-1 (P ¼ 0.02) and EEF1A2 (P ¼ 0.01). To extend these findings, we then studied 11 tissue microarray blocks comprising normal and tumor tissue specimens from 113 patients with pathologic stage I non-small-cell lung cancer who had undergone curative surgery (Wang et al, 2005). Immunohistochemical analysis showed that EEF1A2 was expressed in 32 cases (28%) and KCIP-1 in 29 cases (26%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive Ki-67 expression was found to correlate with positive expression of both KCIP-1 (P ¼ 0.02) and EEF1A2 (P ¼ 0.01). To extend these findings, we then studied 11 tissue microarray blocks comprising normal and tumor tissue specimens from 113 patients with pathologic stage I non-small-cell lung cancer who had undergone curative surgery (Wang et al, 2005). Immunohistochemical analysis showed that EEF1A2 was expressed in 32 cases (28%) and KCIP-1 in 29 cases (26%).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence in situ hybridization and immunohistochemical analyses of lung tissue microarrays Fluorescence in situ hybridizations and immunohistochemical analyses of KCIP-1 and EEF1A2 were carried out as described elsewhere (Jiang et al, 2002;Wang et al, 2005) with Lung Tissue Microarrays (Ambion, Austin, TX, USA) and 11 homemade microarray blocks containing tissue samples from 113 patients with pathologic stage I non-small-cell lung cancer (Wang et al, 2005). DNA probes specific for KCIP-1 and EEF1A2 were obtained by screening a Human BAC Clone library (Invitrogen) by polymerase chain reaction as described previously (Jiang et al, 2002).…”
mentioning
confidence: 99%
“…Early studies suggested that S100A2 expression is suppressed at an early stage of lung carcinogenesis [37], but later data indicated that it might be strongly expressed in the majority of NSCLC tumours [37,38]. In the most recent studies, it was proposed that over-expression of the S100A2 gene in stage I NSCLC indicates a poor prognosis, and may be used to identify patients with early-stage NSCLC [39], or even as a predictor of distant metastasis [40]. There could also be differences in the levels of expression according to the NSCLC type [38].…”
Section: Introductionmentioning
confidence: 99%
“…28 --31 Furthermore, overexpression of S100A2 was identified as a potential prognostic marker for poor disease-specific survival in patients with stage I NSCLC and pancreatic cancer. 9,11 Hypermethylation of the promoter region is a common mechanism of gene silencing. 32 --36 Site-specific DNA methylation of the S100A2 gene promoter in tumorigenic breast cancer cell lines has been shown to correlate with S100A2 repression during breast cancer progression.…”
Section: Resultsmentioning
confidence: 99%